Genetic ancestry is associated with subclinical cardiovascular disease in African Americans and Hispanics from the Multi-Ethnic Study of Atherosclerosis (MESA) - Wassel, Christina L. (2009)
BACKGROUND: Differences in cardiovascular disease (CVD) burden exist among racial/ethnic groups in the United States, with African Americans having the highest prevalence. Subclinical CVD measures have also been shown to differ by race/ethnicity. In the United States, there has been significant intermixing among racial/ethnic groups creating admixed populations. Very little research exists on the relationship of genetic ancestry and subclinical CVD measures. METHODS AND RESULTS: These associations were investigated in 712 African-American and 705 Hispanic participants from the MESA candidate gene sub-study. Individual ancestry was estimated from 199 genetic markers using STRUCTURE. Associations of ancestry and coronary artery calcium (CAC) and common and internal carotid intima media thickness (cIMT) were evaluated using log-binomial and linear regression models. Splines indicated linear associations of ancestry with subclinical CVD measures in African-Americans, but presence of threshold effects in Hispanics. Among African Americans, each standard deviation (SD) increase in European ancestry was associated with an 8% (95% CI (1.02, 1.15), p=0.01) greater CAC prevalence. Each SD increase in European ancestry was also associated with a 2% (95% CI (−3.4%, −0.5%), p=0.008) lower common cIMT in African Americans. Among Hispanics, the highest tertile of European ancestry was associated with a 34% greater CAC prevalence, p=0.02 as compared to lowest tertile. CONCLUSIONS: The linear association of ancestry and subclinical CVD suggests that genetic effects may be important in determining CAC and cIMT among African-Americans. Our results also suggest that CAC and common cIMT may be important phenotypes for further study with admixture mapping.